PEMANFAATAN MEDIA AUDIO VISUAL UNTUK PEROLEHAN KETERAMPILAN MEMBACA SYAIR DI KELAS VII SMP MUHAMMADIYAH 2 KETAPANG - Nurhajijah, Nurhajijah; Astuti, Indri; Martono, Martono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this research are : 1) how lingustic learning design with the use of media in learning audio visual for the skill reading syair in class VII students of SMP Muhammadiyah 2 Ketapang?, 2) How do measures of media use in learning audio visual for the skill reading syair in class VII students of SMP Muhammadiyah 2 Ketapang?, 3) How does the evaluation of learning skill reading syair with the use of media in class VII students of SMP Muhammadiyah 2 Ketapang?. The purpose if this study to know clearly about : 1) design linguistic learning with the use of media in learning audio visual for skill reading syair in class VII students of SMP Muhammadiyah 2 Ketapang, 2) measures of media use in learning linguistic audio visual for skill reading syair, 3) implementation evaluation of learning with the skill reading syair use of media audio visual. The approach used in this research is descriptive qualitative approach. Acquisition of data through interviews, observation, and documentation, the media used in the study is a audio visual, while the instrument is a teacher and class VII students of SMP Muhammadiyah 2 Ketapang. Based on the research that has been done shows increased students learning behaviors that include cognitive, affective, and psychomotor with an average score of 86 ( very good category). Thus, learning process can utilize media audio visual.Keywords : Media Audio Visual, linguistic education, syair.